Child labor, sex and mental health outcomes amongst adolescent refugees. (June 2020) - Meyer, Sarah R.; Yu, Gary; Rieders, Eliana; Stark, Lindsay
Abstract: Introduction: Refugee adolescents living in camps and settlements in low and middle-income countries are a vulnerable population who face protection and psychosocial risks. This study explores prevalence of child labor amongst adolescent refugees from South Sudan in two refugee settlements in Uganda, to understand impacts of child labor on mental health outcomes, and examines the influence of sex on these impacts. Methods: Surveys were conducted in Adjumani and Kiryandongo refugee settlements, Uganda, with 470 adolescents between 13 and 17 interviewed between December 2014–February 2015. Univariate finite mixture modeling identified a two-cluster model of child labor. Logistic regression models assessed the association of child labor and mental health. Results: A two-cluster solution for child labor activity was determined among the 332 adolescents who self-reported engaging in any child labor (Significant child labor: n = 174, 37%; moderate child labor cluster: n = 158, 34%; no child labor cluster: n = 138, 29%. Odds of depression amongst adolescents exposed to significant vs. no child labor was 4.15 (95% CI: 2.01–8.56), in a model examining interaction of sex and child labor and controlling for socio-demographic variables. For the anxiety outcome, girls exposed to significant vs. no child labor are less likely to report higher levels of anxiety (OR: 0.29, 95% CI: 0.09–0.90). Conclusions: Adolescents living in refugee settlements in Uganda report high levels of participation in child labor. Protection of adolescents from the risks involved with child labor in refugee contexts is an important and often over-looked area of child protection in humanitarian settings.